The Efficacy and Safety of Tolvaptan in Heart Failure Patients with Congestive Signs: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mei Zeng; Na Li; Tongshuai Chen; Yun Ti; Chunmei Zhang; Peili Bu (Cardiology Discovery)
Objective:. The aim of this study was to investigate the efficacy and safety of tolvaptan, as well as the impact of its treatment dose and duration in heart failure patients with congestive signs. Methods:. The PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were searched to collect data from all randomized controlled trials (RCT) examining the efficacy and safety of tolvaptan in heart failure patients with congestive signs compared with placebo or blank control until March 4, 2021. Urine volume, change in body weight, improvement in dyspnea, and reduction of edema were evaluated as efficacy indicators. All-cause mortality, worsening heart failure, and adverse events were considered safety indicators. The quality of eligible publications was assessed using the Cochrane risk of bias for RCTs. Results:. Ten RCTs with 5,980 patients were included in this analysis. Compared with control, tolvaptan significantly reduced weight in the short term (day 1, 7 RCTs, weighted mean difference (WMD): –1.09, 95% confidence interval (CI): –1.27 to –0.91; day 2, 2 RCTs, WMD: –1.67, 95% CI: –3.00 to –0.33; day 7, 4 RCTs, WMD: –0.95, 95% CI: –1.25 to –0.66), increased urine volume (WMD: 1,825.72, 95% CI: 1,438.38–2,213.07), and relieved dyspnea (risk ratio (RR): 1.12, 95% CI: 1.05–1.19) without increasing the mortality rate (RR: 0.96, 95% CI: 0.87–1.06). Furthermore, the weight loss and increase in urine volume were not dose-dependent effects, and prolonged medication did not lead to sustained weight loss. In addition, there seemed to be more adverse events (RR: 1.17, 95% CI: 1.03–1.32) after treatment with tolvaptan. Further analysis revealed that patients treated with tolvaptan were more likely to report thirst (RR: 6.09, 95% CI: 3.37–11.00) and dry mouth (RR: 6.36, 95% CI: 4.09–9.90), as well as develop hypernatremia (RR: 12.76, 95% CI: 3.52–46.32). Conclusions:. The meta-analysis shows that tolvaptan can improve congestion with no increase in mortality rate, but should be used to guard against adverse events. Deserve to be mentioned, the number of RCTs included was limited, suggesting that the observed results should be interpreted with caution. Additional robust clinical studies are warranted to validate the present findings.